Impact of SGLT2 inhibitors on heart failure risk and kidney function in type 2 diabetic mellitus patients: A literature review - Chelsy Vanya Br. Meliala; Syahrul Tuba; Adi Priyono; Syed Azhar Syed Sulaiman; Budi Sumaryono; Endah Permata Sari (FoundAE, 2026)
Background: Type 2 diabetes mellitus is known to be closely associated with an increased risk of heart failure and chronic kidney disease, both of which are major causes of illness and death in diabetic patients. In recent years, sodium-glucose cotransporter-2 inhibitors (SGLT2i), which were initially developed as blood glucose-lowering drugs, have been shown to provide additional benefits beyond glycemic control, particularly in protecting the heart and kidneys. Aims: This literature review aims to comprehensively evaluate the impact of SGLT2 inhibitor use on the risk of heart failure and renal function outcomes in patients with type 2 diabetes mellitus (T2DM). Method: A literature search was conducted through the PubMed, Scopus, and ScienceDirect databases for publications from 2015 to 2025, including randomized controlled trials (RCTs), meta-analyses, and systematic reviews using the keywords